Interviewing in Action in a Multicultural World - Murphy, Bianca Cody
You can learn best when you read about skills; view seasoned clinicians using the skills with clients; and practice the skills through role-plays and skill application exercises, while receiving feedback from instructors and peers. That's the complete package that you get with INTERVIEWING IN ACTION IN A MULTICULTURAL WORLD, Third Edition. The authors give you the clinical wisdom and hands-on practice to fully develop your clinical interviewing skills. INTERVIEWING IN ACTION illustrates how you can promote change over time using the client-clinician relationship as momentum for growth. When you use all elements of this integrated learning package together--the text, the DVD with video clips, and the companion website with self-exploration activities and essay questions--you'll learn quickly, easily, and you'll be able to see and do just like working clinicians